Yamato 980459: Mineralogy and petrology of a new shergottite-related rock from Antarctica - Mikouchi,Takashi; Koizumi,Eisuke; McKay,Gordon; Monkawa,Akira; Ueda,Yuji; Chokai,Jun; Miyamoto,Masamichi (National Institute of Polar Research, 2004)
P(論文) Y980459, a new Martian meteorite from Antarctica, is composed of coarse porphyritic olivine grains (up to 2mm) set in the groundmass of olivine and pyroxene with abundant glassy mesostasis containing dendritic olivine and pyroxene. The overall petrography of Y980459 is similar to those of olivine-phyric shergottites, but the absence of plagioclase and Ca phosphates makes Y980459 unique. Because of the absence of maskelynite, Y980459 is not a shergottite if we employ the classic definition of shergottite. Both olivine and pyroxenes are extensively zoned. The most magnesian olivine composition is Fo86 and the olivine compositions are related to three different occurrence types of olivine (large phenocrysts, groundmass, and mesostasis). Pyroxenes have orthopyroxene cores (En81Fs17Wo2) mantled by pigeonite with the rims of augite. The mineralogy of Y980459 suggests that rapid crystallization of the parent magma caused significant undercooling and plagioclase did not nucleate. Probably, rapid transport of the Y980459 parent magma from the depth to the Martian surface crystallized olivine and pyroxene at first and eruption onto the surface quenched the magma producing the glassy mesostasis. Because olivine and pyroxene compositions of Y980459 are the most magnesian among Martian meteorites, Y980459 would represent one of the most primitive Martian magmas and derive from a highly reduced mantle. It seems that Y980459 contains no cumulus component, suggesting that Y980459 is a melt. In this sense, Y980459 is similar to QUE94201. The similarity in mineralogy and chemistry between Y980459 and olivine-phyric shergottites suggests derivation from a similar highly reduced mantle. However, Y980459 was the only sample that directly erupted onto the Martian surface without any accumulation processes. departmental bulletin paper